2021
DOI: 10.1111/1346-8138.16022
|View full text |Cite
|
Sign up to set email alerts
|

Patient characteristics and burden of disease in Japanese patients with generalized pustular psoriasis: Results from the Medical Data Vision claims database

Abstract: Generalized pustular psoriasis (GPP) is a rare, severe, neutrophilic skin disease characterized by episodes of widespread eruption of sterile, visible pustules, which can occur with or without systemic inflammation and with or without plaque psoriasis. 1,2 GPP is associated with potentially life-threatening systemic complications including sepsis and cardiac failure, and is described by the Japan Ministry of Health as an intractable disease. [1][2][3][4] Mutations in IL36RN, CARD14, or AP1S3 have been found in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
87
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(103 citation statements)
references
References 24 publications
11
87
5
Order By: Relevance
“…It has been suggested that there may be a female preponderance in GPP; however, the extent of this varies by geographical region and between ethnicities. A study in 102 patients from Malaysia reported a 2:1 ratio of GPP in females versus males; a study of 74 patients in the US reported a 1.03:1 ratio; and in a study of over 700 patients in Japan, 51.5% were female [ 9 , 10 , 14 ]. Findings from a recent inpatient database of 1516 people with GPP in Japan reported that 56% were male, and a registry in Western Japan observed that 52% of 102 GPP cases were male [ 15 , 16 ].…”
Section: Disease Characteristics Of Gppmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that there may be a female preponderance in GPP; however, the extent of this varies by geographical region and between ethnicities. A study in 102 patients from Malaysia reported a 2:1 ratio of GPP in females versus males; a study of 74 patients in the US reported a 1.03:1 ratio; and in a study of over 700 patients in Japan, 51.5% were female [ 9 , 10 , 14 ]. Findings from a recent inpatient database of 1516 people with GPP in Japan reported that 56% were male, and a registry in Western Japan observed that 52% of 102 GPP cases were male [ 15 , 16 ].…”
Section: Disease Characteristics Of Gppmentioning
confidence: 99%
“…There was a slight female preponderance in patients with GPP (51.5%) compared with those with plaque psoriasis, in which a minority of patients were female (38.7%). Patients with GPP were more likely to have comorbidities than patients with plaque psoriasis; these comorbidities included hypertension, peptic ulcer disease, osteoporosis, type 2 diabetes, gout, psoriatic arthritis, chronic obstructive pulmonary disease, obesity, asthma, insomnia, interstitial pneumonia, thyroid disorders, and other forms of psoriasis [ 14 ]. These findings suggested that patients with GPP in Japan had a higher disease burden than those with psoriasis vulgaris [ 37 ].…”
Section: Adding Evidence To the Understanding Of Gpp Disease Characteristics And Prevalencementioning
confidence: 99%
“…Like moderate-to-severe psoriasis, GPP is associated with an increased occurrence of comorbidities compared to the general population. 4 Comorbidities that have been reported in GPP include obesity, hypertension, hyperlipidemia, diabetes, uveitis, 4–7 cholestasis, 8 joint involvement, 4–7 , 9 , 10 allergic rhinoconjunctivitis and peptic ulcer disease. 4 , 7 …”
Section: Introductionmentioning
confidence: 99%
“…Patients with GPP have a higher burden of illness than those with plaque psoriasis [30]. Important complications of acute phase GPP, some of which can be induced by drugs used to treat this disease (e.g.…”
Section: Burden Of Diseasementioning
confidence: 99%
“…A recent retrospective database analysis conducted in Japan showed that, compared with patients with plaque psoriasis (N = 27,773), patients with GPP (N = 718) were more likely to experience comorbidities and to be prescribed antibiotics and psychiatric medication, and required more healthcare resource utilization and longer hospital stays [30]. Not surprisingly, GPP has a notable impact on a patient's QoL, although data quantifying this impact are lacking.…”
Section: Burden Of Diseasementioning
confidence: 99%